Phytochemical and Organoleptic Tests of Combined Extracts of Turmeric, Black Tea, and Ginger - Rosyidah, Rara Annisaur; Andrianto, Dimas (Current Biochemistry, 2024)
Phytochemical screening to conduct a preliminary evaluation of the chemical content of black tea (Camellia sinensis), Turmeric (Curcuma longa), and Ginger (Zingiber officinale). In addition, the content of secondary metabolites in black tea, turmeric and ginger can be used as an indication of the quality of these plants. the need for a combination of black tea extract act, turmeric, and ginger from various people so that it can be liked by the public. This study aims to test the phytochemical extracts of black tea, turmeric, and ginger as well as organoleptic tests on the most optimum combination of -glucosidase enzyme inhibitory activity. Phytochemical screening showed that black tea and ginger extract contains alkaloids, flavonoids, tannins, saponins, terpenoids, quinones, glycosides, and phenolics, while turmeric extract contains alkaloids, flavonoids, tannins, terpenoids, quinones, glycosides, and phenolics. The organoleptic test of the F7 combination consisting of a combination of black tea extract, turmeric, and ginger showed the highest level of preference by P3 and P2 on color, aroma, consistency, and aftertaste, while taste was at P3.